The microtonical intonation range in Kakataibo singing: a phonetic and musicological approach to no bana ‘iti - Prieto Mendoza, Alejandro (2021)
In this article we propose a phonetic and musicological analysis of the traditional no bana ‘iti song of the Kakataibo, a group of the Pano linguistic family of the Peruvian Amazon, in order to contrast the results with what has been said by several authors about microtonalism as a characteristic of the song mentioned above. Based on the phonetic and musical analysis of the same, unlike other previous studies, which propose the existence of microtonic variations and a melody composed of two or three notes, in the present study we consider that the no bana ‘iti song is composed of two fluctuating notes: a first one being high (H), which falls on the first syllable and a second deep low one (L), which is associated with the rest of the melodic line. Finally, we will study the interaction of these two fluctuating notes with the Kakataibo meter and we will apply this proposal to the ñoxakwati song as an example for future analysis.